Synthesis and evaluation of mechanical properties for coconut fiber composites-A review. (2021) - Shravan Kumar, Nutenki; Buddi, Tanya; Anitha Lakshmi, A.; Durga Rajesh, K.V.
Abstract: Natural fibre composites are being replaced conventional materials because of its Eco-Friendly, renewable source & biodegradable nature, over artificial composites. Composite is a material which is made up of combination of two (or) more components or materials together to form a new one with higher strength. Natural fibre composites are the material fabricated by using either any one or both of the matrix and reinforcement, using from natural sources which are biodegradable. In this chapter, the recent reports about the properties, fabrication process, applications and advancements in the field of composites fabricated with coconut fibre reinforced composites has been discussed. These natural composites will be created at a low cost, having practically identical mechanical properties with other composites and maintains balance between ecology, technology and economy. This helps to replace non-biodegradable composites, which are beneficial to the consumer.